Efektifitas Digitalisasi Arsip Surat Melalui Pembuatan Aplikasi Document Management System (DMS) Pada Subbagian Tata Usaha Kantor Kementerian Agama Kota Lhokseumawe - Nova Amalia (LPPM-UNIKI, 2022)
Archived is defined as a place for data or information in the form of document-based writing stored in a container that is generally made by the agency to be used as a data recapitulation when needed. The Ministry of Religion Office in Lhokseumawe City has been using a manual method of letter archiving up until recently, requiring personnel to fill out each letter individually, identifying the intended recipient, the type of letter, and the actions that will be performed on it. Using a manual filing system has many negative impacts on various aspects like terms of security which can lead to potential data loss. In addition, the document search process takes a long time. This greatly affects the quality of services provided by the Administrative Subdivision at the Office of the Ministry of Religion of the City of Lhokseumawe to the community and also to the Organization. Therefore, this research produces a Document Management System (DMS) application that can facilitate the archiving process and digital correspondence system. Keywords: Archieved; Digitization; Document Management System; Letter.